THE PERFORMANCE OF VAPOR COMPRESSION REFRIGERATION SYSTEM USING R-1270 - Kamin Sumardi; Ega Taqwali Berman; Mutaufiq Mutaufiq (Universitas Sultan Ageng Tirtayasa, 2021)
The use of environmentally friendly refrigerants as working fluids in vapor compression refrigeration systems can prevent global warming effects and depletion of the ozone layer. This research aims to obtain data on the performance of the vapor compression refrigeration systems that use R-1270. Refrigerant R-1270 is categorized into the hydrocarbon (HC) group that is environmentally friendly with ODP = zero and GWP <3. Tests were conducted on vapor compression refrigeration system that consisted of a domestic refrigerator (RD) and a chest freezer (CF). The parameters measured in this research were: refrigeration effect, compression work, weight of refrigerant circulated, electricity consumption, coefficient of performance, and the time required to reach the lowest evaporator temperature. In testing, the first step was to conduct a test on the vapor compression refrigeration system that used baseline refrigerant (R-134a) with a weight according to the manufacturer’s recommendations. Then, the second step was to test the performance of the vapor compression refrigeration system that used R-1270 with a mass of 30% of baseline. The test was conducted for 300 minutes by recording the observed data at every 30-minute interval. The results showed that the replacement of baseline refrigerant by R-1270 was able to increase the coefficient of performance of the vapor compression refrigeration system by 13% - 56% and reduce electricity consumption by 13.5% - 19%. This research has implications for the work of compressors that becomes easier and cheaper energy costs.